Analysis of the Housing Situation in Poland and the European Union Countries - Marcin SUROWKA; Joanna WYROBEK (Communications of International Proceedings, 2020)
The publication aimed to compare the Polish housing market situation with the situation in other European Union countries. The authors verified the hypothesis that Poland's situation is one of the worst in the EU when it comes to overcrowding, the number of young people without their own dwellings, housing availability, housing standards, and accessibility of mortgage.
Keywords: Housing; Real Estate; European Union.